“What is sacred is danced”: an approach to the Xavante ontology from an analysis of four dances involved in the adolescent’s initiation ritual - Román Molero, Massiel (2021)
Based on the analysis of four dances, this work intends to make a first approach and reflect on the following question: in what way the dances involved in the initiation ritual –and with them, their experience as a dancing body– of the Wapté- Xavante form it ontologically? The hypothesis that we maintain is that in these dances the ontological transformation that the boy has to experience is expressed. In this ontology, some capacities are developed: the ability to deal with one’s own body weight and integrate the dialectic between light and heavy into one’s own movement; the ability to repeat and, with it, to be able to move between the poles of differentiation and identity; the abilities to listen, think, observe and remember dreams; and the ability to bond emotionally to his age group. But these ontological characteristics are reached because of the experience of limits and suffering; In other words, it is through the limits that the Xavante becomes a full person.